Quality management of the chemical-technological process for continuous synthesis of pharmaceutical substances of medicinal compounds in flow microreactors - V. F. Kornyushko; O. M. Nikolaeva; A. V. Panov; R. R. Biglov; A. S. Kuznetsov (Тонкие химические технологии)
Objectives. The introduction of digital tools for the development of medicines, intelligent management systems, and quality control is stipulated not only by modern requirements for the chemical and pharmaceutical industry but also by strict regulatory requirements for manufactured products. This principle ensures the release of a quality product on the first attempt. The aim of this study is to develop information support for the intelligent quality management system for the production of active pharmaceutical substances (APSs) for medicines using a fundamentally new technology: continuous synthesis in flow microreactors. To develop the necessary information support, we developed appropriate systemic, informational, and mathematical models; algorithms for the online management of the experiment; and techniques and algorithms to qualitatively assess whether the product meets official regulatory documents.Methods. System analysis techniques, information and mathematical modeling techniques with multireference regression models, and online optimization using the Hook–Jeevs algorithm (a method of expert evaluation based on the concordance factor) were used to solve the problems formulated.Results. To manage the quality of the process of continuous APS synthesis in the flow microreactor, we developed theoretic multiple system models that were designed to build the digital information environment for the process of experimental research. We developed algorithms for mathematical modeling and optimization of the control process based on multiresponse regression models and an online optimization algorithm that allows the process to be managed step by step, taking into account the limitations. Our results show that the degree of conversion is higher in reactions that contain bromodiphenylmethan.Conclusions. Based on mathematical modeling method algorithms for the quality control of the process of continuous APS synthesis on a fundamentally new microreactor system, Qmix were developed. The applicability of the proposed methods and algorithms in the production of the drug diphenhydramine from chlorobenzohydrol and bromobenzohydrol as initial substances was proven by an experimental study. The built models were statistically adequate and valid.